2012
DOI: 10.1017/s0031182012001679
|View full text |Cite
|
Sign up to set email alerts
|

Helminth communities of fish as ecological indicators of lake health

Abstract: This paper deals largely with the dynamics and changes in the helminth parasite communities of fish along the trophic gradient of lakes. The use of parasitological community data as a bioindicator of environmental health underlines the need to study parasite communities at comparable localities with known pollution levels. The comparison of the conditions in different habitats might be helpful to differentiate between normal fluctuations in ambient conditions and pollution-mediated effects. Therefore, the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Indeed, glochidia were absent in Gunn Creek, suggesting that freshwater clams may be infrequent or absent in this system; a similar trend was seen in pulp-effluent polluted lakes in Finland by Valtonen et al (1997). Increased nutrient loading associated with high proportions of agriculture may also facilitate an increase in snail density (Shah et al, 2013). This could explain the increase in Posthodiplostomum spp.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Indeed, glochidia were absent in Gunn Creek, suggesting that freshwater clams may be infrequent or absent in this system; a similar trend was seen in pulp-effluent polluted lakes in Finland by Valtonen et al (1997). Increased nutrient loading associated with high proportions of agriculture may also facilitate an increase in snail density (Shah et al, 2013). This could explain the increase in Posthodiplostomum spp.…”
Section: Discussionmentioning
confidence: 54%
“…and Physella sp. as the first intermediate host (Hoffman, 1956), so increased abundance of this parasite may indicate an increase in number or density of snails (Shah et al, 2013). In contrast, the lifecycle of Actinocleidus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creek suggests potential alteration of invertebrate transmission pathways (Marcogliese 2004 Creek was absent of glochidium, suggesting that freshwater clams are infrequent or absent in this system; a similar trend was seen in pulpeffluent polluted lakes in Finland by Valtonen et al (1997). Increased nutrient loading associated with high proportions of agriculture may however create increased densities of snails (Shah et al 2013), which could potentially explain the increase in Posthodiplostomum ssp. prevalence and intensity with increasing habitat degradation compared to other species.…”
Section: Discussionmentioning
confidence: 61%
“…I anticipated areas with increased benthic diversity and lower watershed disturbance would have higher species diversity, a trend that has been demonstrated in previous research (e.g. Valtonen et al 1997;Shah et al 2013). In Chapter 4, the findings from Chapters 2 and 3 will be integrated and discussed, and potential avenues for future research and applications of results found here will be presented.…”
Section: Research Objectivesmentioning
confidence: 58%